PEMBINAAN PENDIDIKAN KARAKTER PADA SISWA MADRASAH ALIYAH PONDOK PESANTREN AL AZHAR PAGAR ALAM - Darminah Darminah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2016)
This study raised concerns about the development of character education to students of Madrasah AliyahPondok Pesantren Al Azhar Pagaralam. This study uses qualitative research methods to understand thephenomenon of what is experienced by research subjects. Data collection techniques used wereinterviews, observation and documentation. From the results of this study indicate that the formation ofstudent character education in Madrasah Aliyah Al Azhar Pagaralam use persuasion, persuasion cancreate intimacy between chaplain to students. With this persuasive approach students easily understandand accept the advice of teachers, so teraplikasikan with deeds and good behavior in their daily lives.Methods in Development of Education character of students in Madrasah Aliyah Al Azhar Pagaralamusing the exemplary methods, such as the example of the Prophet and his companions, in the hopestudents can emulate aspects of attitudes and actions in daily life. Implementation approaches andmethods of coaching morals students have a positive impact, because the methods and approaches usedare relevant and appropriate to the conditions of students.